"The role of L. reuteri DSM17938 in nutritional recovery and treatment of constipation in children and adolescents with anorexia nervosa - a randomized, double blind, placebo controlled study". (December 2021) - Žaja, Orjena; Fiolić, Maja; Ćuk, Matea Crnković; Tiljak, Mirjana Kujundžić
Summary: Background: Anorexia nervosa (AN) carries the risk of potentially irreversible medical complications, especially in children and adolescents. Constipation is frequent and difficult to manage. Due to the symptoms it causes, constipation can further compromise nutritional rehabilitation. Objective: To investigate the role of probiotics ( Lactobacillus reuteri DSM 17938) in children and adolescent with AN. Design, setting and participants: Randomized, double blind, placebo controlled study in 31 female pediatric AN patients with constipation, referred to nutritional therapy in Pediatric Gastroenterology Department, Sestre milosrdnice University Hospital Centre in Zagreb. Methods: At hospitalization, patients were randomly assigned into two groups; one taking L. reuteri, and other placebo for 3 months, along with the conventional nutritional rehabilitation. Patients were followed 3 months after stopping the treatment. The primary outcome was relief of constipation, assessed after 3 months, while secondary outcomes were normalization of body weight, stool frequency and consistency, relief of dyspepsia, weight gain and recovery of malnutrition regarding bone density and vitamin D3 levels. Results: The study showed statistically significant difference between the two groups considering the stool frequency (6.4 vs. 4.2 stools/week; p < 0.05) and normalization of body weight (93 vs. 63%; p = 0.04) after 6 months, but no significant effect on the rate of relief of constipation (87 vs. 64%; p = 0.22) at 3 months. In the L. reuteri group, the normalization of BMD was achieved in 8/15, whereas in the placebo group, in 3/16 patients. However, there was no statistically significant difference compared to the placebo group regarding the BMD recovery as well as the normalization of D3 levels (p = 0.056). Conclusions: Probiotics may serve as simple and safe adjuvant therapy of constipation in childhood AN and contribute to faster nutritional recovery. Although a statistically significant difference between the two group in relief of constipation could not be shown after 3 months, a benefit from probiotics could be in increasing stool frequency and nutritional recovery in childhood AN after six months. Registered under ClinicalTrials.gov Identifier no. NCT02004288.